2011
DOI: 10.2478/v10172-011-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Babbitt Bushes in Steam Turbine Sliding Bearings

Abstract: The analysis of the properties of babbitt bushes is presented in this article. Materials intended for examinations were charged from the TK-120 steam turbine of TG-8 turbosystem from the Power Station Stalowa Wola. The specimens were subsequently tested for Brinell hardness, microhardness, bending strength and wear resistance. The wear tests were carried out using the block-on-ring tester. The samples were also investigated by means of both light microscopy (LM) and scanning electron microscopy (SEM).Keywords:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…It is also characterized by good impact strength and shows susceptibility to bending stresses initiated by changes in the direction of rotation and edge pressure [5,6]. The tribological properties of this alloy can be improved, among others, by refinement and changes in the morphology of precipitates present in the alloy, as confirmed by earlier studies done by the authors of this article [5].…”
Section: Introductionsupporting
confidence: 55%
“…It is also characterized by good impact strength and shows susceptibility to bending stresses initiated by changes in the direction of rotation and edge pressure [5,6]. The tribological properties of this alloy can be improved, among others, by refinement and changes in the morphology of precipitates present in the alloy, as confirmed by earlier studies done by the authors of this article [5].…”
Section: Introductionsupporting
confidence: 55%
“…The microhardness of the modified Babbitt was 53% higher than that of the heated Babbitt, which could be attributed to the refined SnSb intermetallic uniformly distributed on the Babbitt matrix. 19
Figure 5.Microhardness of the bare Babbitt, heated Babbitt, and modified Babbitt.
…”
Section: Resultsmentioning
confidence: 99%
“…In the case of indentation, the smaller the indentation, the harder the material; confirming the increase in the hardness of the UNSM-treated specimen. Leszczynska-Madej and Madej have reported on the mechanism of hardness increase in Babbitt alloys [ 24 ]. They found that the increase in hardness of Babbitt alloys may be attributed to the presence of a hard SnSb phase in the form of squares in the microstructure and the occurrence of fine precipitates uniformly distributed over the whole Sn matrix.…”
Section: Resultsmentioning
confidence: 99%